2015
DOI: 10.1002/hep.27703
|View full text |Cite
|
Sign up to set email alerts
|

Should surgery be carried out in patients with hepatocellular carcinoma with portal hypertension?

Abstract: We read with great interest the meta-analysis by Berzigotti et al. 1 This study revealed that clinically significant portal hypertension (CSPH) significantly increased the 3-and 5-year mortality rates and risks of clinical liver decompensation after surgery on hepatocellular carcinoma (HCC) patients with cirrhosis and portal hypertension. We appreciate their hard work in coming up with this systematic review and meta-analysis. However, as hepatic surgeons, we would like to raise the following points:1. Postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…47 Similarly, several other reports argue that HVPG > 10 mm Hg should not be considered an absolute contraindication to resection. 42,[48][49][50][51] Response to Therapy for Portal Hypertension…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…47 Similarly, several other reports argue that HVPG > 10 mm Hg should not be considered an absolute contraindication to resection. 42,[48][49][50][51] Response to Therapy for Portal Hypertension…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…A meta-analysis demonstrated that the presence of CSPH evaluated by direct or surrogate measurements was significantly associated with the higher risk of 3- and 5-year mortality and of hepatic decompensation after HR for HCC [ 7 ]. But these results were not regarded as convincing evidence mainly due to the differences of definitions or evaluations of CSPH, BCLC stage and endpoints in studies included [ 15 , 16 ].…”
Section: The Value Of Hvpg In Hcc Prognosis After Hrmentioning
confidence: 99%
“…The EASL and AASLD guidelines for the management of HCC consider CSPH to be a contraindication for HR [ 2 , 3 ] due to the higher risk of postoperative liver decompensation based on the reports of BCLC group [ 4 , 5 ]. However, there is no consensus regarding how CSPH should be evaluated in the decision-making process, but most researches hold the view that CSPH should not be considered an absolute contraindication to HR [ 12 , 15 , 16 , 19 ].…”
Section: The Value Of Hvpg In Hcc Prognosis After Hrmentioning
confidence: 99%
See 1 more Smart Citation
“…This reflects remarkable advances in radiological technology [13] , [14] , surgical techniques, and perioperative care. However, some liver care centers and official guidelines in the West do not recommend hepatic resection for such patients [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] .…”
Section: Introductionmentioning
confidence: 99%